Enhancing Interpretative Reading Comprehension and Reading Interest through RADEC Integrated with Canva and Forms: A Quasi-Experimental Study in Indonesian Primary Schools - Cindy Cindhana Brilliananda; Ivana Septia Rahaya; Onasis Silalahi (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to examine the effectiveness of the RADEC (Read–Answer–Discuss–Explain–Create) learning model integrated with Canva and Google Forms in improving elementary students’ interpretative reading comprehension and reading interest. A quasi-experimental design with a non-equivalent control group was employed, involving 99 fifth-grade students. Data were collected using essay-based tests and a Likert-scale questionnaire and analyzed using MANOVA. The results showed no significant difference at the pretest stage (p > 0.05), indicating comparable baseline conditions between groups. However, the posttest results revealed a significant difference (p < 0.001), confirming the effectiveness of the intervention. The experimental group demonstrated higher improvement in interpretative reading comprehension (gain = 6.06) and reading interest (gain = 8.57) compared to the control group. Effect size analysis indicated large effects (partial eta squared = 0.168 and 0.213), suggesting substantial practical impact. These findings indicate that the integration of structured inquiry-based learning with multimodal digital tools enhances both cognitive and affective dimensions of literacy. This study contributes to the development of technology-integrated pedagogy by demonstrating the effectiveness of combining the RADEC model with digital platforms to support higher-order reading skills and student engagement in primary education.